Participatory gender-responsive monitoring of women land rights: empowering and smart. Issue 7 (2nd October 2016) - Lecoutere, Els
ABSTRACT: This viewpoint argues that a genuine participatory approach to defining a theory of change and outcome indicators of enhanced women land and property rights is essential to include the standpoint of women and men who are directly involved, and to acknowledge their power to frame the change and solutions they envision. Moreover, outcomes and outcome indicators defined by women and men who are targeted by women rights interventions typically better distinguish outcomes to be reached among women, among men, and in terms of gender relations, are more concrete and easier to measure.